Foot and ankle problems in Muay Thai Kickboxers - Tanawat Vaseenon (2018)
© 2015, Medical Association of Thailand. All rights reserved. Background: Muay Thai kickboxing is a common sport that uses the foot and ankle in fighting. Muay Thai kickboxing trainees usually receive training in Thailand. Foot and ankle problems in this group of people who usually train barefoot remain unexplored. Objective: To evaluate the prevalence of common foot and ankle problems in Muay Thai kick boxers. Material and Method: The present study is a cross-sectional survey of Muay Thai kick boxers practicing in northern Thailand. Interviews were conducted and foot and ankle examinations were evaluated. Foot morphology was examined using a Harris mat footprint. Results: One hundred and twenty-three Muay Thai kickbox ersinnine training gyms were included in this study. Common foot and ankle problems found in the Muay Thai kick boxers were callosity (59%), gastrocnemius contracture (57%), toe deformities (49.3%), wounds (10%) and heel pain (9%). Callosity was most commonly found on the forefoot (77.5%), on the plantar first metatarsal (55.3%) and on the big toe (33.3%). An association was found between a tight heel cord and a history of foot injury with prolonged periods of weekly training. Toe deformities such as hallux rigidus (37.6%) were also associated with prolonged periods of training (p = 0.001). No correlation was found between type of foot arch and foot and ankle problems. Conclusion: Plantar forefoot callosities and wounds as well as toe deformities including tight heel cords are some of the foot and ankle problems commonly found in Muay Thai kick boxers. They are associated with prolonged periods of barefoot training. The unique pattern of training and of the kicks in Muay Thai might be a path mechanism, leading to the development of foot and ankle problems.